Does firm size matter in export, technology, and marketing activities of Indian garment firms? - Rasiah, R.; Kaur, K.; Kumar, A. (Korean Soc Innovation Management & Econ-Kosime, 2010)
This article examines statistical differences in export, technological, and marketing intensities between large enterprises (LEs), and small and medium enterprises (SMEs) in the garment manufacturing industry in India. Results show that SMEs enjoy higher export and research and development (R&D) intensities than LEs even after controlling for ownership, wages, and age. Compared with SMEs, LEs enjoy higher technological (including human resource and process technology) and marketing intensities even after controlling for ownership, wages, and age. Despite showing lower technological and marketing intensities, SMEs are characterised by a positive and strong relationship between their export intensity, and R&D and marketing intensities. Despite enjoying higher technological and marketing intensities, LEs show a modest relationship between their export intensity, and R&D and marketing intensities. Results also suggest that SMEs are more strongly integrated with the global garment value chains as outsourcing firms compared with LEs.